2017
DOI: 10.1155/2017/8610353
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Decision Analysis of Spectrum Management Frameworks for Futuristic Wireless Networks: The Context of Developing Countries

Abstract: National regulatory authorities (NRAs) in developing countries need an accelerated means to formulate technical regulations for the telecommunications sector. This will enable countries to gain maximum benefits from the rapid advances in technology. The existing regulation-making processes are time-consuming and do not cope with the emergence of global technological changes. This article presents an efficient and quicker approach to formulate regulatory framework to govern the wireless technologies that are ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In [325], the role of national regulation authorities (NRAs) in promoting the use of TVWS is discussed. An approach for multi-criteria decision analysis to evaluate spectrum management frameworks was proposed and used to evaluate the Federal Communications Commission (FCC)…”
Section: B Spectrum and Economical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [325], the role of national regulation authorities (NRAs) in promoting the use of TVWS is discussed. An approach for multi-criteria decision analysis to evaluate spectrum management frameworks was proposed and used to evaluate the Federal Communications Commission (FCC)…”
Section: B Spectrum and Economical Aspectsmentioning
confidence: 99%
“…in the United States of America (USA) and Ofcom (UK) frameworks for dynamic spectrum management. It was found that it is preferable to keep tight control on the geo-location spectrum database by operating it by the NRA, in order to more efficiently protect the TV users from secondary access, while allowing license-exempt spectrum access to secondary users [325].…”
Section: B Spectrum and Economical Aspectsmentioning
confidence: 99%
“…The paper [Mfupe et al, 2017] (PROMETHÉE) presents a modelling approach for formulating a regulatory framework to govern the spectrum utilization by wireless networks that are based on the Dynamic Spectrum Access (DSA) technique; for the evaluation of the DSA management policies of regulatory authorities, a multi-attribute analysis model with eleven criteria, including socio-economic objectives, is presented and tackled with a PROMETHÉE method in [Brans & Mareschal, 2005].…”
Section: Strategic Planning and Policy Issuesmentioning
confidence: 99%
“…In [251], the role of national regulation authorities (NRAs) in promoting the use of TVWS is discussed. An approach for multi-criteria decision analysis to evaluate spectrum management frameworks was proposed and used to evaluate the Federal Communications Commission (FCC) in the USA and Ofcom (UK) frameworks for dynamic spectrum management.…”
Section: Spectrum and Economical Aspectsmentioning
confidence: 99%
“…An approach for multi-criteria decision analysis to evaluate spectrum management frameworks was proposed and used to evaluate the Federal Communications Commission (FCC) in the USA and Ofcom (UK) frameworks for dynamic spectrum management. It was found that it is preferable to keep tight control on the geolocation spectrum database by operating it by the NRA, in order to more efficiently protect the TV users from secondary access, while allowing license-exempt spectrum access to secondary users [251]. Similarly, in [252], TVWS spectrum regulations in several countries were discussed, and it was noted that many developing countries, notably in Africa, where the TVWS spectrum is the most available, are lagging behind developed countries in terms of spectrum regulation.…”
Section: Spectrum and Economical Aspectsmentioning
confidence: 99%